First report of cassava witches’ broom disease and Ceratobasidium theobromae in the Americas - Pardo, J. M; Gil-Ordoñez, A.; Leiva, A. M.; Enjelvin, L.; Chourrot, A.; Kime, S. C. K.; Demade‐Pellorce, L.; Marchand, M.; Wilson, V.; Jeandel, C.; Ioos, R.; Cuellar, W. J. (Wiley, 2024)
Cassava (Manihot esculenta) is a primary source of carbohydrates for millions of people in the tropics. In the Americas, cassava also holds deep cultural and economic significance for indigenous peoples (Parmar et al., 2017). However, the increased commercialisation and connectivity between cassava-producing regions has heightened the risks of the introduction of diseases that threaten this food security crop. Symptoms of dwarfism, weak sprouts with short petioles and vascular necrosis were observed since 2023 in cassava-growing communes in French Guiana (Table 1). These symptoms resembled those of cassava witches’ broom disease (CWBD) which has previously been reported only in Southeast Asia (Pardo et al., 2023) (Fig. 1). Recently, CWBD was associated with Ceratobasidium theobromae (Leiva et al., 2023; Landicho et al., 2024), the fungus causing vascular streak dieback of cacao (Keane et al., 1972). To characterise the disease, on 13 May, 2024, we visited SaintGeorges-de-l’Oyapock (N3.731375, -W51.788637), the commune that had the largest number of affected fields in our previous survey (Table 1; Fig. 1). Petioles of the top part of cassava plants with and without symptoms were collected following a diagonal transect along the field (code name GUF-114). Petioles were wrapped in paper towels, placed in plastic bags, and kept at 4◦C for 24 hours before processing. For fungus isolation, petioles were disinfected using 1% hypochlo-rite followed by 75% ethanol following the protocol described by Gil-Ordóñez et al. (2024). For DNA extraction dry petioles were transferred into 2 mL tubes and ground in liquid nitrogen before using a DNeasy Plant Mini Kit (Qiagen, Germany). The rDNA internal transcribed spacer region was amplified using ITS4 and ITS5 primers (Landicho et al., 2024). A phylogenetic tree was generated using the Maximum Likelihood method (1000 replicates) with related sequences available in GenBank. PCR specific to C. theobromae targeting the CAMK gene, was conducted as described by Leiva et al. (2023).